Answer

Verified

60.9k+ views

Hint: Equation of line parallel to the common axis is given by \[y=c\].

Let’s consider the two parabolas \[{{y}^{2}}=4ax\] and \[{{y}^{2}}=-4bx\].

From the equation of the parabola, we can see that the axis of the parabolas is common and their concavities are opposite.

Now, we know the equation of the common axis is \[y=0\].

So, the equation of a line parallel to the common axis is \[y=c\].

Now, this line meets the parabolas \[{y}^{2}=4ax\] and \[{y}^{2}=-4bx\] at \[P\] and \[{{P}^{'}}\] respectively.

Let the midpoint of \[P{{P}^{'}}\] be \[\left( h,k \right)....\left( i \right)\].

Now, substituting \[y=c\] in \[{y}^{2}=4ax\], we get:

\[{{c}^{2}}=4ax\]

\[\Rightarrow x=\dfrac{{{c}^{2}}}{4a}\]

So, the point \[P\] is \[\left( \dfrac{{{c}^{2}}}{4a},c \right)\].

Substituting \[y=c\] in \[y=-4bx\], we get:

\[{{c}^{2}}=-4ax\]

\[\Rightarrow x=\dfrac{-{{c}^{2}}}{4b}\]

So, the coordinates of \[{{P}^{'}}\] are \[\left( \dfrac{-{{c}^{2}}}{4b},c \right)\].

Now, know that the coordinates of the midpoint of the line joining two points \[\left( {{x}_{1}},{{y}_{1}} \right)\] and \[\left( {{x}_{2}},{{y}_{2}} \right)\] is given as:\[\left( \dfrac{{{x}_{1}}+{{x}_{2}}}{2},\dfrac{{{y}_{1}}+{{y}_{2}}}{2} \right)\]

So, the midpoint of \[P{{P}^{'}}\] is

\[\left( \dfrac{\dfrac{{{c}^{2}}}{4a}-\dfrac{{{c}^{2}}}{4b}}{2},\dfrac{c+c}{2} \right)\]

\[=\left( \dfrac{{{c}^{2}}}{8a}-\dfrac{{{c}^{2}}}{8b},c \right)....\left( ii \right)\]

From \[\left( i \right)\]and \[\left( ii \right)\], we can conclude that

\[h=\dfrac{{{c}^{2}}}{8a}-\dfrac{{{c}^{2}}}{8b}\] and \[k=c\]

Or, \[h=\dfrac{{{k}^{2}}}{8a}-\dfrac{{{k}^{2}}}{8b}\]

Or, \[h=\dfrac{{{k}^{2}}}{8}\left( \dfrac{1}{a}-\dfrac{1}{b} \right)\]

Or, \[h=\dfrac{{{k}^{2}}}{8}\left( \dfrac{b-a}{ab} \right)\]

Or, \[\dfrac{8h\left( ab \right)}{a-b}={{k}^{2}}\]

Or \[{{k}^{2}}=\dfrac{8ab}{b-a}.h\]

Or \[{{k}^{2}}=4\left( \dfrac{2ab}{b-a} \right).h\]

Replacing \[k\] by \[y\]and \[h\] by \[x\], we get:

\[{{y}^{2}}=4\left( \dfrac{2ab}{b-a} \right).x\]

which clearly represents a parabola.

Hence, the locus of the midpoint of \[PP'\] is the parabola \[{{y}^{2}}=4\left( \dfrac{2ab}{b-a} \right).x\].

Now, in case if the latera recta of the parabolas are equal then:

We know, length of latus rectum of parabola \[{{y}^{2}}=4ax\] is \[4a\] and the length of latus rectum of parabola \[{{y}^{2}}=-4bx\] is \[4b\].

If the latera recta are equal, then

\[4a=4b\]

\[\Rightarrow a=b\]

\[\Rightarrow b-a=0\]

Now, when we substitute \[b-a=0\] in the equation of locus, we get

\[{{y}^{2}}=4\left( \dfrac{2ab}{0} \right).x\]

\[\Rightarrow {{y}^{2}}=\infty \] which is an invalid curve.

Hence, for the locus to exist, the latera recta of the two parabolas must be unequal.

So, the locus of \[P{{P}^{'}}\]is a parabola , given by \[{{y}^{2}}=4\left( \dfrac{2ab}{b-a} \right).x\], which exists only when the latera recta of the given two parabolas are unequal.

Note: Remember that the midpoint of two points \[\left( {{x}_{1}},{{y}_{1}} \right)\] and \[\left( {{x}_{2}},{{y}_{2}} \right)\]is given as \[\left( \dfrac{{{x}_{1}}+{{x}_{2}}}{2},\dfrac{{{y}_{1}}+{{y}_{2}}}{2} \right)\]. Students generally make a mistake of writing it as \[\left( \dfrac{{{x}_{1}}-{{x}_{2}}}{2},\dfrac{{{y}_{1}}-{{y}_{2}}}{2} \right)\].

Let’s consider the two parabolas \[{{y}^{2}}=4ax\] and \[{{y}^{2}}=-4bx\].

From the equation of the parabola, we can see that the axis of the parabolas is common and their concavities are opposite.

Now, we know the equation of the common axis is \[y=0\].

So, the equation of a line parallel to the common axis is \[y=c\].

Now, this line meets the parabolas \[{y}^{2}=4ax\] and \[{y}^{2}=-4bx\] at \[P\] and \[{{P}^{'}}\] respectively.

Let the midpoint of \[P{{P}^{'}}\] be \[\left( h,k \right)....\left( i \right)\].

Now, substituting \[y=c\] in \[{y}^{2}=4ax\], we get:

\[{{c}^{2}}=4ax\]

\[\Rightarrow x=\dfrac{{{c}^{2}}}{4a}\]

So, the point \[P\] is \[\left( \dfrac{{{c}^{2}}}{4a},c \right)\].

Substituting \[y=c\] in \[y=-4bx\], we get:

\[{{c}^{2}}=-4ax\]

\[\Rightarrow x=\dfrac{-{{c}^{2}}}{4b}\]

So, the coordinates of \[{{P}^{'}}\] are \[\left( \dfrac{-{{c}^{2}}}{4b},c \right)\].

Now, know that the coordinates of the midpoint of the line joining two points \[\left( {{x}_{1}},{{y}_{1}} \right)\] and \[\left( {{x}_{2}},{{y}_{2}} \right)\] is given as:\[\left( \dfrac{{{x}_{1}}+{{x}_{2}}}{2},\dfrac{{{y}_{1}}+{{y}_{2}}}{2} \right)\]

So, the midpoint of \[P{{P}^{'}}\] is

\[\left( \dfrac{\dfrac{{{c}^{2}}}{4a}-\dfrac{{{c}^{2}}}{4b}}{2},\dfrac{c+c}{2} \right)\]

\[=\left( \dfrac{{{c}^{2}}}{8a}-\dfrac{{{c}^{2}}}{8b},c \right)....\left( ii \right)\]

From \[\left( i \right)\]and \[\left( ii \right)\], we can conclude that

\[h=\dfrac{{{c}^{2}}}{8a}-\dfrac{{{c}^{2}}}{8b}\] and \[k=c\]

Or, \[h=\dfrac{{{k}^{2}}}{8a}-\dfrac{{{k}^{2}}}{8b}\]

Or, \[h=\dfrac{{{k}^{2}}}{8}\left( \dfrac{1}{a}-\dfrac{1}{b} \right)\]

Or, \[h=\dfrac{{{k}^{2}}}{8}\left( \dfrac{b-a}{ab} \right)\]

Or, \[\dfrac{8h\left( ab \right)}{a-b}={{k}^{2}}\]

Or \[{{k}^{2}}=\dfrac{8ab}{b-a}.h\]

Or \[{{k}^{2}}=4\left( \dfrac{2ab}{b-a} \right).h\]

Replacing \[k\] by \[y\]and \[h\] by \[x\], we get:

\[{{y}^{2}}=4\left( \dfrac{2ab}{b-a} \right).x\]

which clearly represents a parabola.

Hence, the locus of the midpoint of \[PP'\] is the parabola \[{{y}^{2}}=4\left( \dfrac{2ab}{b-a} \right).x\].

Now, in case if the latera recta of the parabolas are equal then:

We know, length of latus rectum of parabola \[{{y}^{2}}=4ax\] is \[4a\] and the length of latus rectum of parabola \[{{y}^{2}}=-4bx\] is \[4b\].

If the latera recta are equal, then

\[4a=4b\]

\[\Rightarrow a=b\]

\[\Rightarrow b-a=0\]

Now, when we substitute \[b-a=0\] in the equation of locus, we get

\[{{y}^{2}}=4\left( \dfrac{2ab}{0} \right).x\]

\[\Rightarrow {{y}^{2}}=\infty \] which is an invalid curve.

Hence, for the locus to exist, the latera recta of the two parabolas must be unequal.

So, the locus of \[P{{P}^{'}}\]is a parabola , given by \[{{y}^{2}}=4\left( \dfrac{2ab}{b-a} \right).x\], which exists only when the latera recta of the given two parabolas are unequal.

Note: Remember that the midpoint of two points \[\left( {{x}_{1}},{{y}_{1}} \right)\] and \[\left( {{x}_{2}},{{y}_{2}} \right)\]is given as \[\left( \dfrac{{{x}_{1}}+{{x}_{2}}}{2},\dfrac{{{y}_{1}}+{{y}_{2}}}{2} \right)\]. Students generally make a mistake of writing it as \[\left( \dfrac{{{x}_{1}}-{{x}_{2}}}{2},\dfrac{{{y}_{1}}-{{y}_{2}}}{2} \right)\].

Recently Updated Pages

Write a composition in approximately 450 500 words class 10 english JEE_Main

Arrange the sentences P Q R between S1 and S5 such class 10 english JEE_Main

What is the common property of the oxides CONO and class 10 chemistry JEE_Main

What happens when dilute hydrochloric acid is added class 10 chemistry JEE_Main

If four points A63B 35C4 2 and Dx3x are given in such class 10 maths JEE_Main

The area of square inscribed in a circle of diameter class 10 maths JEE_Main

Other Pages

The resultant of vec A and vec B is perpendicular to class 11 physics JEE_Main

A pilot in a plane wants to go 500km towards the north class 11 physics JEE_Main

If a wire of resistance R is stretched to double of class 12 physics JEE_Main

Electric field due to uniformly charged sphere class 12 physics JEE_Main

A train passes an electric post in 10 second and a class 11 physics JEE_Main

Differentiate between homogeneous and heterogeneous class 12 chemistry JEE_Main